2015
DOI: 10.1136/gutjnl-2014-308008
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre comparative prospective blinded analysis of EUS and MRI for screening of pancreatic cancer in high-risk individuals

Abstract: EUS and/or MRI detected clinically relevant pancreatic lesions in 6% of HRI. Both imaging techniques were complementary rather than interchangeable: contrary to EUS, MRI was found to be very sensitive for the detection of cystic lesions of any size; MRI, however, might have some important limitations with regard to the timely detection of solid lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 25 publications
3
122
1
3
Order By: Relevance
“…In the present study 53% (134/253) of IAR revealed mostly cystic pancreatic lesions. This high prevalence of cystic lesions in IAR is in line with three previous MRI and EUS-based prospective studies that reported pancreatic lesions in 33–45% of IAR 9 10 15…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study 53% (134/253) of IAR revealed mostly cystic pancreatic lesions. This high prevalence of cystic lesions in IAR is in line with three previous MRI and EUS-based prospective studies that reported pancreatic lesions in 33–45% of IAR 9 10 15…”
Section: Discussionsupporting
confidence: 91%
“…The recent CAPS consensus summit, as well as several other authors suggested that annual MRI plus MRCP and EUS are currently the best imaging tests for the detection of significant PDAC precursor lesions 2 7 8 10 11 15. The present study also confirms the effectiveness of this screening approach.…”
Section: Discussionsupporting
confidence: 84%
“…The feasibility and cost-effectiveness of this approach has already been shown in recent screening protocols applied to members of families with familial pancreatic cancer (FPC) and patients with select germline mutations. [7][8][9][10][11] However, only 10-20% of all cases of PDA can be attributed to FPC; the vast majority of PDA arise sporadically with limited family history of this disease. 12 The epidemiological association between diabetes mellitus and PDA has been reported in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this consensus, most experts agreed in EUS and MRI/MRCP being the preferred method of screening for pancreatic cancer (83.7 and 73.5%, respectively), since these are the most sensitive in detecting pancreatic lesions and provide no ionizing radiation to patients. It is important to note that these methods are even more sensitive for small, cystic lesions and that they are complimentary rather than interchangeable [11,13].…”
mentioning
confidence: 99%